2021
DOI: 10.1108/pijpsm-03-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of propensity to trust on the perception of police: an integrated framework of legitimacy perspective

Abstract: PurposeThe study aims to examine whether a baseline trait-level characteristic, in this case propensity to trust, impacts peoples' perception of procedural justice, police legitimacy, trustworthiness, obligation to obey and cooperation.Design/methodology/approachUsing Hamm and colleagues' (2017) integrated framework of legitimacy (IFL) as the theoretical framework, the current research explores whether individual trait characteristic differences matter. Using a Korean survey in 2019 with 2188 samples aged 19 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“….” Quantitative survey results show that two-thirds (69%) of participants do not respect, trust , and have confidence in the police and only one-third (31%) of public respect, trust, and have faith in the police. Similarly, during the qualitative interviews, participants revealed: “I do not trust the police because police were involved during the 1987 coup”; “police officers are involved in buying and selling drugs”; “police revealed my name to the offenders when I told police about offenders”; and “police favour their family members, friends, and rich people.” In the literature, Adla et al (2017), Lee and Lee (2021), Morris (2015), and Howes et al (2021) found that if the public does not respect, trust and have confidence in the police; then they are more likely not to cooperate with the police.…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“….” Quantitative survey results show that two-thirds (69%) of participants do not respect, trust , and have confidence in the police and only one-third (31%) of public respect, trust, and have faith in the police. Similarly, during the qualitative interviews, participants revealed: “I do not trust the police because police were involved during the 1987 coup”; “police officers are involved in buying and selling drugs”; “police revealed my name to the offenders when I told police about offenders”; and “police favour their family members, friends, and rich people.” In the literature, Adla et al (2017), Lee and Lee (2021), Morris (2015), and Howes et al (2021) found that if the public does not respect, trust and have confidence in the police; then they are more likely not to cooperate with the police.…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“…Furthermore, Lee and Cho (2020) suggested that procedural justice had a very limited influence on the citizens' perception of legitimacy. Conversely, a few recent studies have concluded that procedural justice was a significant and primary predictor of legitimacy (Lee and Lee, 2021; Lee et al ., 2022a, b). In sum, police legitimacy research in South Korea is inconclusive and requires further exhaustive investigation.…”
Section: Literaturementioning
confidence: 99%
“…Boateng and Buckner, 2019; Boateng et al ., 2022; Bradford et al ., 2014; Gau, 2015; Jackson et al ., 2012; Murphy et al ., 2014; Reisig et al ., 2014; Sun et al ., 2018), most of the research still focused on procedural justice as the main predictor of police legitimacy. In particular, past research on procedural justice examined macro-level predictors such as neighborhood context (Liu et al ., 2020; Reisig et al ., 2021; Sprott and Doob, 2009), micro-level factors such as fear of crime (Kautt, 2011; Liu and Wu, 2023), the propensity to trust (Lee and Lee, 2021) and demographic characteristics like age, gender, education and socio-economic status (Hsieh and Boateng, 2015). Although past literature added to the knowledge of the relationship between procedural justice and the perception of legitimacy, we believe the legitimacy literature needs to be expanded.…”
Section: Introductionmentioning
confidence: 99%
“…Citizens constantly and actively evaluate the behavior of law enforcement and the views of legitimacy citizens hold of the police may be withdrawn if police behavior ceases to conform to the widely accepted norms of fairness (Milani & Jackson,217). Lee and Lee (2021) listed four stages of police legitimacy: (1) interaction, (2) evaluation, (3)…”
Section: Citizens' Perceptions Of Police Legitimacymentioning
confidence: 99%
“…Some cooperate out of fear of jail, and others cooperate because they see them as legitimate. Lee and Lee (2021) argue that citizens cooperate with the police for normative and instrumental reasons. Normative concerns include personal views (how a person feels they should behave) and legitimacy (views of whether police have authority over them) influence cooperation (p. 1108).…”
Section: Citizens' Cooperation With Law Enforcementmentioning
confidence: 99%